Ação anti-fúngica e imunomoduladora de Punica granatumL. assegura a sobrevida na sepse por Candidaalbicans - ALVES, Patrícia Costa Santos (2018)
Sepsis can be characterized as an inflammatory response induced by an infectious agent and Candida albicans is one of the fungi most commonly associated with sepsis, mainly in immunosuppressed patients. We investigated the effect of the standardized extract of the peels of the fruits of Punicagranatum L. (EPG) on lethal sepsis model induced by C. albicans in immunosuppressed mice. We initially established the model of lethal sepsis by C. albicans in outbred mice, since only there were models with inbred lineage. We then evaluated the effects of EPG as an anti-Candida agent and its action on survival and activation of the immune system in immunosuppressed mice with cyclophosphamide. We observed that the inoculum of 3x108 CFU / ml of C. albicans was lethal to all animals within 3 days. However, treatment with EPG reversed this lethality and ensured the survival of all animals, possibly due to their antifungal action. Treatment with EPG reversed immunosuppression, increasing cellularity in the cord and the number of neutrophils in the peritoneum. In the spleen despite no increase in total number of cells, we detected an increase in the number of helper T lymphocytes and activated B lymphocytes. In addition, EPG treatment reduced the production of nitric oxide (NO) and oxygen peroxide (H2O2) and increased the production of IL-17, IL-6 and TNF-α. We conclude that EPG is a promising extract in the search for agents to treat sepsis by C. albicans due to its antimicrobial and immunomodulatory effects, since in a single dose it was able to simultaneously control the lethal sepsis induced by C. albicans and to reverse the immunosuppression caused by the use of cyclophosphamide and activating Th1 and Th17 lymphocytes, activities that may be related to the high content of phenolic compounds, and especially punicalagin and ellagic acid, present in the extract.